Marine Ornamental Species : (Iowa State Press, 2003)
Marine Ornamental Species: Collection, Culture and Conservation is a comprehensive resource containing information on the growing and economically important marine ornamental industry. Experts address current issues from a global perspective, covering the full-range of topics from world economics and product demand to aquatic animal health to ethnic and social/cultural concerns.